Pelaksanaan Koreksi Arah Kiblat Masjid di Kota Banjar oleh Badan Hisab Rukyat Daerah (BHRD) - Ila Nurmila (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2021)
This research was motivated by the implementation of the correction of the direction of the mosque's Qibla by the Regional Hisab Rukyat Agency of Banjar City to determine whether the Qibla direction of the mosque in Purwaharja District, Banjar City and to follow up on the fatwa decision of the Indonesian Ulema Council number 05 of 2010 regarding the Qibla direction. The Banjar City Regional Hisab Rukyat Agency corrected the Qibla direction of the mosque in Purwaharja District, Banjar City. The purpose of this study was to determine the implementation of the correction of the mosque's Qibla direction and the responses and legal basis of the DKM leaders in Purwaharja District to the results of the correction of the mosque's Qibla direction. From the results of the research and discussion of this thesis, it can be concluded that the City of Banjar, including Purwaharja District, is located at 07° 23' South Latitude and 108° 32' East Longitude, so the angle of the Qibla direction is 25° 4' from the West point to the North or 64 ° 56' from the point North to the West. After re-measurement/correction of the mosque's Qibla direction by the Banjar City Regional Hisab Rukyat Agency, it turned out that of the ten mosques in Purwaharja District the Qibla direction was not right, although there were two mosques whose Qibla direction was approaching 25° from the West point to the North. . But the heads of DKM in Purwaharja District gave a good response, meaning that they agreed to the implementation of the correction of the direction of the mosque's Qibla by the Hisab Rukyat Board of Banjar City and they followed up the results of the correction by rearranging the rows/rows in the implementation of prayer services.